2016
DOI: 10.1016/j.aott.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of flatfoot among school students and its relationship with BMI

Abstract: ObjectiveThe aim of this study was to analyze the relation between the flat-footedness and obesity.Materials and MethodsA total of 1158 school children (653 male and 505 female) participated in this cross sectional descriptive study. According to their age, children were divided into three groups for each gender (6–10, 11–13, 14–18 years old). Diagnosis and severity of flatfoot was assessed in using the Dennis method. BMI of children were calculated as body weight divided by height squared (kg*m−2).ResultsMajo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 15 publications
4
52
0
5
Order By: Relevance
“…Our results are consistent with other studies, which reported a relatively high prevalence of overweight, and obesity among children aged 6-12 years. 12,14,15 In this study, BMI correlated positively with flat foot among school-age children. The prevalence for flatfoot was significantly higher in schoolchildren with obesity (52%, P=0.001), overweight (31.25%, P=0.01), and low weight (33.3 %, p=0.01) compared to the prevalence of flat foot (17.2 %) in children with normal weight.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…Our results are consistent with other studies, which reported a relatively high prevalence of overweight, and obesity among children aged 6-12 years. 12,14,15 In this study, BMI correlated positively with flat foot among school-age children. The prevalence for flatfoot was significantly higher in schoolchildren with obesity (52%, P=0.001), overweight (31.25%, P=0.01), and low weight (33.3 %, p=0.01) compared to the prevalence of flat foot (17.2 %) in children with normal weight.…”
Section: Discussionsupporting
confidence: 47%
“…Consistent with current results, previous research found flat foot in 52% of boys and 36% of girls aged 3-6 years old. 12,[21][22][23][24] This study showed that 43.6% of the subjects had an abnormal change in BMI. The prevalence of increased BMI was 33.3% in overweight and 62.5% in obese schoolchildren, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations